SWOT Analysis of Aryakibansland Tourist Destination Development Using 3A Tourism Components (Attraction, Accessibility and Amenity) - Dikky Nur Hidayat Dikky; Romy Rizki Hasbianur; Sarah Lutfiani; Asni Komalasari (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2024)
Purpose: The purpose of This study aims to analyze the development of Aryakibansland tourist attractions using the 3A tourism components: Attractions, Accessibility, and Amenity at Aryakibansland. Method: This research uses a descriptive qualitative approach with data collection methods through observation and literature study. Qualitative research was chosen because it is in accordance with the research objectives that want to observe and analyze the development of aryakibansland tourist attraction. The data obtained was then analyzed using SWOT analysis (Strength, Weakness, Opportunity, & Treath). Result: Based on the results of the study, it can be concluded that the development of Aryakibans Land tourist attraction can be done by using the 3A tourism component (Attraction, Accessibility, and Amenity) in an effort to develop its tourist attraction, among others: Aryakibans Land develops natural and artificial potential to the maximum, adds travel route instructions to get to the tourist attractions, and adds more supporting facilities, such as: gazebos, security posts, places to eat. As for the SWOT analysis strategy carried out is to strengthen the brand of tourist attractions with promotions, hold socialization with governments such as the tourism office and the UMKM office to create innovations in tourism that have high economic value, strengthen the safety factor for tourist visitors to feel safe and education about flood mitigation to reduce the impact of flood disaster threats. Contribution: This article contributes to the development of aryakibansland tourism, with the results of the research produced can provide policy recommendations for tourism managers and local governments to develop tourist destinations, such as providing proper infrastructure for tourists so that accessibility aspects can be better, and improving aspects of amenity, such as tourist support facilities need to be reproduced, because this factor can cause tourists to be interested in visiting a tourist destination.